Late Onset Combined Immunodeficiency Presenting with Recurrent Pneumocystis jiroveci Pneumonia - Ilias Papakonstantinou; Ioannis G. Baraboutis; Lazaros Karnesis (Case Reports in Medicine)
Late onset combined immunodeficiency (LOCID) is a recently described variant of common variable immunodeficiency (CVID), involving adult patients presenting with opportunistic infections and/or low CD4+ lymphocyte counts. A 36-year-old male with unremarkable past medical history presented with fever, respiratory failure, and lymphocytopenia. He was found to have Pneumocystis jiroveci pneumonia (PJP), subsequently complicated by recurrent hospital-acquired Pseudomonas aeruginosa pneumonia and immune reconstitution phenomena, attributed to restoration of immunoglobulin levels. Clinicians should be aware of LOCID, which could be confused with HIV infection/AIDS or idiopathic CD4 lymphocytopenia. In the English bibliography there is only one case report, where PJP was the initial presentation of CVID (that case would probably be classified as LOCID). Phenomena of immune reconstitution are described in various settings, including primary immunodeficiency, manifesting as temporary clinical and radiologic deterioration and leading to misperceptions of therapeutic failure and/or presence of alternative/additional diagnoses.